Analysis of the association between glomerular filtration rate, proteinuria and metabolic syndrome in chronic kidney patients based on longitudinal data - Li Guo; Shanshan Guo; Youlan Gong; Jing Li; Jiandong Li (IET Nanobiotechnology)
Abstract Chronic kidney disease (CKD) is a group of chronic diseases caused by kidney damage from multiple causes. Metabolic syndrome (MS) manifests as dysfunction of endothelial cells and chronic functional inflammatory states, and may be involved in pathological changes related to renal impairment. Based on longitudinal data analysis of the association between estimated glomerular filtration rate (eGFR), proteinuria and MS in patients with CKD, this study aims to provide new ideas for the pathophysiological mechanism of CKD and a theoretical basis for the early prevention and effective intervention of MS‐related kidney damage. A total of 126 patients with CKD were divided into non‐MS group and MS group. According to the eGFR level, 126 patients with CKD were divided into G1 group, G2 group, G3a group, G3b group, G4 group and G5 group. Serum markers such as eGFR, urine protein, and triglycerides (TG) were collected. The correlation between eGFR, urine protein and MS‐related indexes was analysed, and the risk factors affecting CKD complicated by MS were analysed. In patients with CKD, the levels of urine protein, abdominal circumference, TG, systolic blood pressure (SBP), diastolic blood pressure (DBP), and fasting blood glucose (FPG) were increased with the course of the disease, but the levels of eGFR and high density lipoprotein (HDL‐C) were decreased (p < 0.05). Abdominal circumference, TG, SBP, DBP, FP were significantly negatively correlated with eGFR, but HDL‐C was positively correlated with eGFR (p < 0.05). Diabetes, hyperlipidemia, UA, and SBP were independent risk factors affecting CKD complicated MS, and eGFR were independent protective factors (p < 0.05). The combination of diabetes, hyperlipidemia, UA, SBP, and eGFR exhibited higher prediction value for the CKD patients complicated by MS. There was a certain correlation between between MS components with eGFR and urinary protein in patients with CKD. The early intervention treatment of MS was helpful in delaying the development of CKD and reducing proteinuria.